Photocatalytic Reverse Semi‐Combustion Driven by Ionic Liquids. Issue 5 (13th February 2019) - Qadir, Muhammad I.; Zanatta, Marcileia; Gil, Eduarda S.; Stassen, Hubert K.; Gonçalves, Paulo; Neto, Brenno A. D.; de Souza, Paulo E. N.; Dupont, Jairton
Abstract: The simple photolysis of CO2 in aqueous solutions to generate CO and/or hydrocarbons and derivatives in the presence of a catalyst is considered to be a clean and efficient approach for utilizing CO2 as a C1 building block. Despite the huge efforts dedicated to this transformation using either semiconductors or homogeneous catalysts, only small improvements of the catalytic activity have been achieved so far. This article reports that simple aqueous solutions of organic salts—denominated as ionic liquids—can efficiently photo‐reduce CO2 to CO without using photosensitizers or sacrificial agents. The system relies on the formation of the [CO2 ] .− intermediate through homolytic C−C bond cleavage in a cation–CO2 adduct of imidazolium‐based ionic liquids (ILs). The system continuously produced CO up to 2.88 mmol g −1 of IL after 40 h of irradiation by using an aqueous solution of 1‐ n ‐butyl‐3‐methylimidazolium‐2‐carboxylate (BMIm.CO2 ) IL, representing an apparent quantum yield of 3.9 %. The organophotocatalytic principles of our system may help to develop more simple and efficient organic materials for the production of solar fuels from CO2 under mild conditions, which represents a real alternative to those based on semiconductors and homogeneous metal‐based catalysts. Abstract : So long semiconductors : Simple aqueous solutions of ionic liquids can efficiently photo‐reduce CO2 to CO without the use of photosensitizers or sacrificial agents. The system relies on the formation of the [CO2 ] .− intermediate through homolytic C−C bond cleavage in a cation–CO2 adduct of imidazolium‐based ionic liquids, thereby eliminating the need for expensive metal‐based semiconductors or exotic materials.